2023
DOI: 10.3390/ph16071015
|View full text |Cite
|
Sign up to set email alerts
|

LC/MS-MS Analysis of Phenolic Compounds in Hyoscyamus albus L. Extract: In Vitro Antidiabetic Activity, In Silico Molecular Docking, and In Vivo Investigation against STZ-Induced Diabetic Mice

Abstract: This study aimed to investigate the chemical composition and antidiabetic properties of cultivated Hyoscyamus albus L. The ethanol extract was analyzed using LC-MS/MS, and 18 distinct phenolic compounds were identified. Among these, p-coumaric acid (6656.8 ± 3.4 µg/g), gallic acid (6516 ± 1.7 µg/g), luteolin (6251.9 ± 1.3 µg/g), apigenin (6209.9 ± 1.1 µg/g), and rutin (5213.9 ± 1.3 µg/g) were identified as the most abundant polyphenolic molecules. In the in vitro antidiabetic experiment, the ability of the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…All these interacting residues fluctuated in the range of 0.4 to 1 Å. Our results were consistent with those determined previously when studying the X-ray crystal structure of α-amylase (2QV4), suggesting the presence of three main amino acids, namely Asp197, Asp300, and Glu233, which are responsible for its catalytic action (in starch-hydrolyzing enzyme) [43][44][45][46][47][48]. Asp197 was proven to act as a catalytic nucleophile during starch hydrolysis; Glu233 amino acid provides an acid-base catalyst role, while Asp300 plays a leading role in optimizing the orientation of the substrate [49,50].…”
Section: Simulationsupporting
confidence: 91%
“…All these interacting residues fluctuated in the range of 0.4 to 1 Å. Our results were consistent with those determined previously when studying the X-ray crystal structure of α-amylase (2QV4), suggesting the presence of three main amino acids, namely Asp197, Asp300, and Glu233, which are responsible for its catalytic action (in starch-hydrolyzing enzyme) [43][44][45][46][47][48]. Asp197 was proven to act as a catalytic nucleophile during starch hydrolysis; Glu233 amino acid provides an acid-base catalyst role, while Asp300 plays a leading role in optimizing the orientation of the substrate [49,50].…”
Section: Simulationsupporting
confidence: 91%
“…Comparing our research results with those of the same type of plant is unnecessary, as our study stands as the inaugural investigation of this particular plant species. Numerous variables, such as ecological and climatic conditions, genotypes, geographic locations, and environmental stress on the investigated plant, can account for the variance in chemical composition among members of this genus [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking studies of polyphenolic compounds have been reported towards human pancreatic alpha-amylase for antidiabetics [11,12]; towards alpha-glucosidase for antidiabetics [12]; towards the main protease enzymes for antivirals [13]; towards βlactoglobulin for antioxidants [14]; towards all non-redundant holo-proteins from the Protein Data Bank for antioxidative, anti-inflammatory, anticarcinogenic, and antimicrobial activities [15]; and towards cyclooxygenases for anti-inflammatory activities [16]. No studies have been reported on tyrosinase for anti-melanogenesis drug discovery.…”
Section: Introductionmentioning
confidence: 99%